Large first hyperpolarizability of the Au@Ag core-shell nanoparticles as compared to the corresponding alloyed nanoparticles resulting from laser annealing - Russier-Antoine, Isabelle; Jonin, Christian; Benichou, Emmanuel; Bertorelle, Franck; Brevet, Pierre-François (Frontiers in Photonics, 2025)
In this work, the first hyperpolarizability of Aux@Ag100-x core-shell nanoparticles with x the gold molar fraction in percent and the gold core of which is 12 nm in diameter, is determined and compared to that of their corresponding laser annealed nanoparticles using hyper Rayleigh scattering experiments. Laser annealing transforms the initially composite Aux@Ag100-x core-shell nanoparticles into alloyed AuxAg100-x homogeneous nanoparticles, providing a reference for comparison. It is observed that the evolution with the relative molar ratio between gold and silver of the first hyperpolarizability magnitude of both the Aux@Ag100-x core-shell and the alloyed AuxAg100-x nanoparticles is driven by the SPR resonance enhancement occurring at the harmonic wavelength due to red shifting of the SPR band away from the harmonic wavelength. Furthermore, the first hyperpolarizability magnitude of the Aux@Ag100-x core-shell nanoparticles is found to be about three orders of magnitude larger than that of the annealed alloyed AuxAg100-x nanoparticles. This feature may be attributed to the existence of the two nonlinearities, namely, the surface nonlinearity due to the surrounding medium–silver layer interface and the silver–gold metal - metal interface constructively contributing due to their close localization. The core-shell morphology is thus highly beneficial in view of applications as compared to the alloyed one.